2009
DOI: 10.1111/j.1751-553x.2008.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the Sysmex XS‐1000i automated haematology analyser

Abstract: The Sysmex XS-1000i is a compact new, fully automated haematology analyser, designed to generate complete blood counts with five-part leucocyte differential. In our study, a Sysmex XS-1000i instrument was evaluated according to Clinical Laboratory Standards Institute (CLSI) and International Council for Standardization in Haematology (ICSH) guidelines. Precision, carry-over and linearity were determined. Using a total of 700 patient samples, results from the Sysmex XS-1000i were compared with those from a Sysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
2
17
0
3
Order By: Relevance
“…This study showed that the analyzer provides reliable and comparable results to instruments that are currently used in clinical laboratories. [9][10][11][12] Overall results of the repeatability and device/method precision satisfied the manufacturer's specifications, except for low PLT. The coefficient of variation at low PLT was slightly higher than the coefficient of variation claimed by the manufacturer, though it was still acceptable according to EP5-A2 specifications.…”
Section: Commentsupporting
confidence: 54%
See 2 more Smart Citations
“…This study showed that the analyzer provides reliable and comparable results to instruments that are currently used in clinical laboratories. [9][10][11][12] Overall results of the repeatability and device/method precision satisfied the manufacturer's specifications, except for low PLT. The coefficient of variation at low PLT was slightly higher than the coefficient of variation claimed by the manufacturer, though it was still acceptable according to EP5-A2 specifications.…”
Section: Commentsupporting
confidence: 54%
“…4 The imprecision of automated platelet counts in the thrombocytopenic range is a welldocumented problem. 11,[13][14][15] The LABGEO HC10 showed an overall good correlation with the LH780, except for MCHC. The poor correlation of MCHC has also been previously reported in the literature.…”
Section: Commentmentioning
confidence: 84%
See 1 more Smart Citation
“…The presence of interfering particles in automated blood cell enumeration often triggers a ‘flag’ for manual review. Although flags are helpful and results in film review, this flagging is often not sensitive enough (resulting in false negatives) or misidentifies other cellular types (resulting in false positives) (Brown et al , 2001; Chin-Yee et al , 2001, 2002; Keeney, Brown & Chin-Yee, 2001; Muller et al , 2006; Ghys, Malfait & J, 2009). Inaccurate automated enumeration of any parameter involves the traditional labor-intensive process of manually inspecting and assessing a peripheral blood film for each of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Modern commercial cell counters [8][9][10][11][12] have reached their limit of analytical potential in cell identification and have a weak performance in cell characterization, i.e., in determination of physical characteristics of cells. In particular, blood platelet volume and refractive index, red blood cell volume, and hemoglobin concentration are the only physical characteristics that can be measured reliably with automatic hematology analyzers.…”
Section: Introductionmentioning
confidence: 99%